Cross-cultural validation of the Weight Stigma Exposure Inventory (WeSEI): secondary data analysis from Taiwan, China, Hong Kong, Indonesia, Türkiye, and Malaysia - Fan, Chia Wei; Ruckwongpatr, Kamolthip; Lin, I. Ching; Chen, I. Hua; Chen, Ji Kang; Nurmala, Ira; Muthmainnah, Muthmainnah; Gan, Wan Ying; Üztemur, Servet; Chang, Yen Ling; Lin, Chien Chin; Christensen, Jeanette Reffstrup; et al. (BioMed Central Ltd, 2025)
Background: The Weight Stigma Exposure Inventory (WeSEI) is a newly developed instrument designed to assess weight stigma exposure across both interpersonal and non-interpersonal contexts. While prior studies have supported its use in individual regions, its cross-cultural applicability has not been comprehensively evaluated. Objective: The present study examined the psychometric properties and cross-cultural measurement equivalence of the WeSEI across six culturally diverse jurisdictional regions in Asia (i.e., Taiwan, China, Hong Kong, Indonesia, Türkiye, and Malaysia). Methods: A total of 7,787 participants completed the 35-item WeSEI via various online platforms. The WeSEI assesses weight stigma exposure across seven domains: social media, traditional media, television/movies, parents/siblings, friends/peers, significant others, and strangers. Rasch analysis was conducted to evaluate item fit, rating scale functioning, person separation reliability, and unidimensionality for each domain. Differential item functioning (DIF) was assessed across sex, weight status, and jurisdictional region. Results: The WeSEI demonstrated strong internal consistency, acceptable item fit, and unidimensionality across all domains, with only two items showing misfit (i.e., Friends/Peers_2 and Significant Other_2). Person separation indices exceeded 2.0 for each domain, confirming the scale’s ability to distinguish individuals with varying levels of stigma exposure. Minimal DIF was observed by sex and weight status, supporting measurement equivalence across these groups. However, 19 out of 35 items showed significant jurisdictional region-level DIF, particularly those related to slim-normative attractiveness and family-based stigma. Malaysian participants consistently endorsed these items more than Chinese participants, suggesting cultural variation in the exposure of weight stigma. Conclusion: The WeSEI is a psychometrically sound and culturally responsive tool for assessing weight stigma exposure across diverse populations in Asia. Cultural adaptation is recommended for cross-national comparisons.